2012
DOI: 10.1016/j.wocn.2012.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Voice onset time is necessary but not always sufficient to describe acquisition of voiced stops: The cases of Greek and Japanese

Abstract: The age at which children master adult-like voiced stops can generally be predicted by voice onset time (VOT): stops with optional short lag are early, those with obligatory lead are late. However, Japanese voiced stops are late despite having a short lag variant, whereas Greek voiced stops are early despite having consistent voicing lead. This cross-sectional study examines the acoustics of word-initial stops produced by English-, Japanese-, and Greek-speaking children aged 2 to 5, to investigate how these se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 47 publications
3
33
0
6
Order By: Relevance
“…This considered, it might be the case that other acoustic cues are being primarily employed in the perception and production of voice distinctions. Similar cases have been discussed in recent studies (SUNDARA, 2005;OH, 2011;KONG;BECKMAN;EDWARDS, 2012), which investigate Canadian French, Korean and Japanese, respectively. In these languages, additional cues, such as burst intensity and fundamental frequency (F0) in the following vowel, take the lead as the main acoustic correlates employed to distinguish voiceless from voiced plosive segments in perception and production.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…This considered, it might be the case that other acoustic cues are being primarily employed in the perception and production of voice distinctions. Similar cases have been discussed in recent studies (SUNDARA, 2005;OH, 2011;KONG;BECKMAN;EDWARDS, 2012), which investigate Canadian French, Korean and Japanese, respectively. In these languages, additional cues, such as burst intensity and fundamental frequency (F0) in the following vowel, take the lead as the main acoustic correlates employed to distinguish voiceless from voiced plosive segments in perception and production.…”
supporting
confidence: 81%
“…As we found out that other acoustic cues were acting as relevant cues, it remains to be investigated which acoustic(s) cue (s) is/are being primarily followed by Brazilian learners in these voice distinctions. As already mentioned, studies by Sundara (2005), Oh (2011) and Kong, Beckman e Edwards (2012) have raised the possibility that both burst intensity and F0 seem to play a decisive role in this sense. What remains to be determined, in further studies, is which of these two acoustic cues plays a more decisive role in Brazilian Portuguese and, as a likely consequence, in Brazilian PortugueseEnglish interlanguage.…”
Section: Final Considerationsmentioning
confidence: 89%
“…It is important to bear in mind, however, that the three stop categories in Korean are all voiceless in utterance-initial position and for some speakers both F0 and voice quality also play a role for the distinction among the three categories (see e.g. Cho, Ladefoged, & Jun, 2002;Han & Weitzman, 1970;Kang & Guion, 2008;Kang, 2014;Kim & Duanmu, 2004;Kong, Beckman, & Edwards, 2012). However, in terms of vowel quality, they look very similar.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on /dz/ variation mainly focused on geographical/dialectal differences [e.g., Ang 洪惟仁 (2003Ang 洪惟仁 ( , 2012, Chang 洪惟仁, 張素蓉 (2008), Chen 陳淑娟 (1995), Chen 陳雅玲 (2010Chen 陳雅玲 ( , 2012, , Hung 洪慧鈺 (2007), Khng 康韶真 (2014), Lin 林珠彩 (1995), Thoo 涂文欽 (2009), and Wang 王薈 雯 (2014)], and little has been discussed on the potential effect of gender. However, as gender has always been a prominent factor for sound changes and variations [e.g., English: Holmes (1999); Japanese: Kong et al (2012); Mandarin: Baran (2014), Fon et al (2011), andZhang (2005); Tibetan: Reynolds (2012); Yami: Rau et al (2009)], it is surmised that there might also be a gender difference in the realization of Min /dz/. Previous research showed that the effect of gender on sound changes is not always straightforward and has more to do with the nature of the change and how it interacts with the two genders (Labov 1990;Maclagan et al 1999;Trudgill 2000).…”
Section: Specific Aimsmentioning
confidence: 99%